Latex of Apocynaceae family plants: A review (Research, Society and Development, 2021)
Plant latex is excreted by the plant's defense system in response to stresses. In certain cases, latex can be toxic, but its use is viable, as its components can have varied biological activities, such as: antibacterial; antitumor; antioxidant; antifungal, anti-inflammatory; larvicide, among others. Different botanical families produce latex, one of the main and most comprehensive is Apocynaceae. Given this scope, it is necessary to carry out studies on the applicability of latex. Thus, this study aimed to promote the search for scientific papers that describe the use of latex species: Calotropis procera (Aiton) W.T. Aiton; Cryptostegia grandiflora R. Br; Cryptostegia madagascariensis Bojer; Hancornia speciosa Gomes; Himatanthus drasticus Mart.; Allamanda blanchetti A. DC. through a literature review. Scientific works were selected under exclusion and inclusion criteria, in the following databases: “CAPES Journals”, “Science Direct”, “Scielo”, “PubMed”, “Google Scholar” and “SciFinder” under a time interval of 37 years (1984-2021), being used works in the languages: English and Portuguese. The results show that the latex of the species can act as: antimicrobial, anthelmintic, antitumor, anticancer, anti-inflammatory, chemotherapeutic, larvicide, insecticide, among other activities. It is concluded that plant latex is a promising source for the synthesis of drugs, repellents, cosmetics, and can stimulate research aimed at the conscious extraction of natural resources.